Reliabilism's Memory Loss. - Frise, Matthew (Philosophical Quarterly, 2021)
Generativism about memory justification is the view that memory can generate epistemic justification. Generativism is gaining popularity, but process reliabilists tend to resist it. Process reliabilism explains the justification of beliefs by way of the reliability of the processes they result from. Some advocates of reliabilism deny various forms of generativism. Other reliabilists reject or remain neutral about only the more extreme forms. I argue that an extreme form of generativism follows from reliabilism. This result weakens a long-standing argument for reliabilism.